A review of arsenic in crops, vegetables, animals and food products. (15th March 2019) - Upadhyay, Munish K.; Shukla, Anurakti; Yadav, Poonam; Srivastava, Sudhakar
Highlights: The major source of arsenic exposure in human is rice and rice-based products. Apart from rice, As levels in other important dietary sources has also been covered. The level of As species (iAs/oAs) influences the associated As toxicity in food. It is mandatory to set the regulatory limits of arsenic in food at earliest. Abstract: Arsenic (As) is a carcinogenic element threatening the health of millions of people around the world. The sources for human exposure include drinking water, crops, processed food items, vegetables, mushrooms, animal products etc. The people at most risk are those living in hotspots of As contamination viz., Bangladesh and West Bengal, India. However, it has been found that rice growing in other uncontaminated regions like Australia can also contain high As levels. Further, rice import/export among various countries make the problem of global concern. The emergence of several reports of As in rice based food products including baby food from different parts of the world demonstrates that even the infants and toddlers are not spared. The variation in the levels of inorganic and organic As species in different food items influence the associated As toxicity. This review tries to present the available data on As levels in various dietary sources.